Introduction to Development Engineering 2022
DOI: 10.1007/978-3-030-86065-3_7
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Industrial Pollution in India

Abstract: Many developing countries are attempting to prevent a rapid deterioration of air quality while still encouraging economic growth. In settings where state capacity is severely limited, enhancing the effectiveness of regulators is critical to success. Previous work has documented how Indian environmental regulators are constrained by having poor information on the pollution emitted by manufacturing plants, due to high monitoring costs, corruption, or staff constraints. This case study discusses a pilot project i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…Another study found that air pollution negatively affects labor productivity and individual consumption [29]. Furthermore, air pollution has been linked to reduced life expectancy, increased disease burden, and other health risks [30]. In the context of Jakarta, increasing green space has been proposed as a way to improve air quality and reduce greenhouse gas emissions [31].…”
Section: Impact On Bpjs Health Budgetmentioning
confidence: 99%
“…Another study found that air pollution negatively affects labor productivity and individual consumption [29]. Furthermore, air pollution has been linked to reduced life expectancy, increased disease burden, and other health risks [30]. In the context of Jakarta, increasing green space has been proposed as a way to improve air quality and reduce greenhouse gas emissions [31].…”
Section: Impact On Bpjs Health Budgetmentioning
confidence: 99%